Patologi Sosial dalam Kumpulan Cerpen Karya Narapidana Perempuan dan Pemanfaatanya sebagai Alternatif Sumber Bahan Ajar Apresiasi Sastra Di SMA - Yuan Malista Ayuseptiwi; Nita Widiati (Universitas Negeri Malang, 2021)
Abstract: This study intends to portray the social pathology contained in a collection of short stories that contain different experiences of women prisoners. To be specific, the focal points of this study are (1) the type of social pathology contained in the collection of short stories by women prisoners, (2) the variables that cause social pathology in the collection of short stories by women prisoners, (3) the utilization of the collection of short stories by women prisoners as an alternative material for the appreciation of literary learning in high school. This study is a qualitative research using descriptive method to see how the social pathology in the collection of short stories by women prisoners by analyzing the collection of short stories. The results of this study indicate that the forms of social pathology contained in this collection of short stories by women prisoners are: 1) crime, 2) gambling, (3) drugs, and, (4) juvenile delinquency. The factors that cause the occurrence of social pathology contained in the collection of short stories by women prisoners consist of 4 (four) things, namely (1) economic factor, (2) family factor, (3) social environmental factor, and (4) psychological factor. This collection of short stories can be used as an alternative source of teaching material because it meets the criteria for a learning material, such as socio-cultural background, psychological aspect, and linguistic aspect. Keywords: social pathology; short stories; literature learning Abstrak: Penelitian ini bertujuan untuk mendeskripsikan patologi sosial yang terdapat dalam kumpulan cerpen yang memuat beragam pengalaman dari para naripadana perempuan. Fokus dalam penelitian ini, yaitu (1) bentuk patologi sosial yang terdapat dalam kumpulan cerpen karya narapidana perempuan, (2) faktor-faktor penyebab terjadinya patologi sosial dalam kumpulan cerpen karya narapidana perempuan, (3) pemanfaatan kumpulan cerpen karya narapidana perempuan sebagai alternatif sumber bahan ajar apresiasi pembelajaran sastra di SMA. Penelitian ini merupakan penelitian kualitatif dengan menggunakan metode deskriptif untuk melihat bagaimana patologi sosial dalam kumpulan cerpen karya narapida perempuan dengan menganalisis kumpulan cerpen tersebut. Hasil penelitian ini menunjukkan bahwa bentuk patologi sosial yang terdapat dalam kumpulan cerpen karya narapidana perempuan ini adalah: 1) kriminalitas, 2) perjudian, (3) narkoba, dan, (4) kenakalan remaja. Faktor-faktor yang menyebabkan terjadinya patologi sosial yang terdapat dalam kumpulan cerpen karya narapidana perempuan terdiri atas 4 (empat) hal yakni (1) faktor ekonomi, (2) faktor keluarga, (3) faktor lingkungan sosial, dan (4) faktor psikologis. Kumpulan cerpen ini dapat dijadikan sebagai alternatif sumber bahan ajar karena memenuhi kriteria pemilihan bahan pembelajaran, serperti latar sosial budaya, aspek psikologis, dan aspek kebahasaannya. Kata kunci: patologi sosial; kumpulan cerpen; pembelajaran sastra